(untitled) (Movimenta (ISSN 1984-4298), 2024)
Introduction: Smartphone usage has grown exponentially in the last decade, is a device that allows the user to solve personal, professional, and other tasks, anywhere. Among teenagers, the emphasis of use is due to social networks, and their ease of communication. However, this practicality may be related to an increasingly sedentary lifestyle, affecting the cardiorespiratory system, thus being a risk factor for future heart disease. Objectives: To investigate the relationship between smartphone overuse and increased physical downtime and predisposition to risk factors for cardiovascular disease. Methods: A cross-sectional observational analytical study was carried out, which followed the STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) methodological strategies. Participants were assessed for habits of mobile technology use, upper limb strength testing, physical fitness, and respiratory capacity. Results: The results showed that excessive smartphone use by adolescents causes decreased physical activity, which can lead to physical inactivity, increased heart rate, and systolic blood pressure. Conclusion: The findings pointed to a direct relationship between increased sedentary behavior. And excessive use of the smartphone, with unfavorable outcomes to the cardiac system.